PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KARYAWAN - Maulidina, Rahma; Muslih, Basthoumi; Purnomo, Hery (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2025)
Research at UD Sumber Muji Mulya has problems, namely the low spirit of cooperation between employees which has an impact on decreasing job satisfaction, non-transparent compensation, and lack of occupational health and safety protection, which risks lowering morale and increasing accidents and occupational diseases. This research uses a quantitative approach with a sample of all UD Sumber Muji Mulya employees. The test results show that OCB has no significant effect partially on employee satisfaction tcount 0.947 < ttable 2.028, and a significance value of 0.350 > 0.05. In contrast, compensation has a significant effect with tcount 2.218 > ttable 2.028, and a significance value of 0.033 < 0.05, as well as the work environment has a significant effect with tcount 2.877 > ttable 2.028, and a significance value of 0.007 < 0.05. Simultaneously, OCB, compensation, and work environment have a significant effect on employee satisfaction at UD Sumber Muji Mulya.